2012
DOI: 10.1371/journal.pone.0036698
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for Children with Immune Thrombocytopenia: A Systematic Review

Abstract: BackgroundRituximab has been widely used off-label as a second line treatment for children with immune thrombocytopenia (ITP). However, its role in the management of pediatric ITP requires clarification. To understand and interpret the available evidence, we conducted a systematic review to assess the efficacy and safety of rituximab for children with ITP.Methodology/Principal FindingsWe searched MEDLINE, EMBASE, Cochrane Library, CBM, CNKI, abstract databases of American Society of Hematology, American Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 38 publications
2
48
0
4
Order By: Relevance
“…33 In addition, 2 systematic reviews have evaluated initial response in children with reported pooled response rates of 57% (N ϭ 116) 34 and 68% (N ϭ 323). 35 Projected 1-and 5-year response rates, however, were significantly lower at 33% and 26%, respectively, for children and 38% and 21%, respectively, for adults. Predictors of response to rituximab include shorter duration of ITP, secondary ITP, and previous response to corticosteroids; however, these have not been consistently identified across studies.…”
Section: Rituximabmentioning
confidence: 90%
See 3 more Smart Citations
“…33 In addition, 2 systematic reviews have evaluated initial response in children with reported pooled response rates of 57% (N ϭ 116) 34 and 68% (N ϭ 323). 35 Projected 1-and 5-year response rates, however, were significantly lower at 33% and 26%, respectively, for children and 38% and 21%, respectively, for adults. Predictors of response to rituximab include shorter duration of ITP, secondary ITP, and previous response to corticosteroids; however, these have not been consistently identified across studies.…”
Section: Rituximabmentioning
confidence: 90%
“…Rituximab has been successful in inducing remission in adults 33,34 and pediatric patients 34,35 with chronic ITP. Two systematic reviews of the adult literature have been published with pooled overall response rates, defined as a platelet count Ͼ 50 ϫ 10 9 /L, of 57% (N ϭ 376) 34 and 63% (N ϭ 313).…”
Section: Rituximabmentioning
confidence: 99%
See 2 more Smart Citations
“…Les recommandations d'experts indiquent leur utilisation en cas d'échec de splénectomie ou comme alternative à celle-ci dans les PTI chroniques [20]. Le taux de réponse global (plaquettes supérieures à 50 G/L) est de 62,5 % chez l'adulte [21] et comparable chez l'enfant [22]. Leur utilisation précoce, comme celle des vinca-alcaloïdes [23] peuvent s'avérer utile dans le PTI pour tenter de restaurer au plus vite un chiffre de plaquettes de sécurité si la thrombopénie est réfractaire à la combinaison corticoïdes/immunoglobulines comme dans les observations de Kim et al récemment publiées [24].…”
Section: Prise En Charge De L'hémorragie Intracrânienne Et Place Des unclassified